2021
DOI: 10.1111/dar.13299
|View full text |Cite
|
Sign up to set email alerts
|

The impact of changes to alcohol policy on patron drinking behaviours in Queensland

Abstract: Introduction. On 1 July 2016, stage 1 of the Tackling Alcohol-Fuelled Violence (TAFV) policy was introduced in Queensland, Australia and included restricted alcohol service to 03:00 in dedicated entertainment precincts (safe night precincts or SNPs). During stage 2 (from 1 February 2017), the number of extended trading permits (i.e. trading until 05:00) per venue were reduced; and during stage 3 (from 1 July 2017), networked identification scanners were mandated for late-night venues. We aim to examine whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Since the Manchester study, international evidence that NTE regulation can reduce harm has increased, most recently with an Australian study. 20–22 That study found that NTE regulation (that includes reduced trading hours) reduced alcohol harms without reducing the number of patrons, scale or diversity of NTEs and occurred while the number of alcohol licensed venues increased. 17 18 62 …”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Since the Manchester study, international evidence that NTE regulation can reduce harm has increased, most recently with an Australian study. 20–22 That study found that NTE regulation (that includes reduced trading hours) reduced alcohol harms without reducing the number of patrons, scale or diversity of NTEs and occurred while the number of alcohol licensed venues increased. 17 18 62 …”
Section: Discussionmentioning
confidence: 97%
“…Manchester study, international evidence that NTE regulation can reduce harm has increased, most recently with an Australian study. [20][21][22] That study found that NTE regulation (that includes reduced trading hours) reduced alcohol harms without reducing the number of patrons, scale or diversity of NTEs and occurred while the number of alcohol licensed venues increased. 17 18 62 This disconnect between stakeholder claims and research evidence raises an important point about the value of examining hypotheses derived from stakeholder opinions, when those opinions may lack supporting evidence or even be contradicted by evidence.…”
Section: Open Accessmentioning
confidence: 96%
See 2 more Smart Citations
“…Approximately seventy to ninety percent of individuals preload with alcohol before a party, event or night-out (Devilly et al, 2019b;Hughes et al, 2008;Merrill et al, 2016). Preloading is often contextualized as a behaviour practiced by young adults (i.e., 18 -24 years;MacLean & Callinan, 2013;Wells et al, 2015), despite a smaller proportion of adults (i.e., 25 -60 years) also reporting engagement in the practice (de Andrade et al, 2021;Devilly et al, 2017). For both individuals young and old, their decisions to preload are guided by various motivations to consume alcohol (LaBrie et al, 2012;Foster & Ferguson, 2014;Devilly et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%